(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article discusses the methodology of teaching a foreign language in higher education. It examines the history of its development as a discipline, the types of modern methods used in the methodology of teaching a foreign language, and the issues of their application.